Bioassay‐guided isolation of anti‐inflammatory constituents from Celtis sinensis leaves. Issue 1 (16th December 2020) - Qi, Zhipeng; Fang, Xianying; Xie, Yingying; Wang, Lei; Zhang, Yiwei; Zhao, Linguo
Abstract: Ginkgo acids (GAs) in ginkgo products usually lead to allergies or liver toxicity. In this study, the GA‐induced toxicity was attenuated and Con A‐induced T‐lymphocyte proliferation was inhibited by extracts of Celtis sinensis leaves (ECSL). So, the active ingredients in ECSL were studied to solve the problems caused by GAs. First, the eight components of MeOH extracts were determined by HPLC‐DAD/LC‐MS. Then, the 12 active ingredients were separated based on the anti‐inflammatory activity. Lymphocyte conversion showed that the inhibition rates of apigenin, quercetin, and isovitexin at 100 μM on Con A‐activated proliferation of T cells were up to 82.46%, 62.86% and 42.76%, respectively. The inhibition rate on the LPS‐induced NO release in RAW 264.7 cells of quercetin, apigenin, isovitexin, and vitexin were exceeding 80% at 100 μM. Taken together, the material foundation for the screen of GAs toxicity‐attenuated ingredients were provided here. Practical applications: Ginkgo biloba extracts (EGBs) have been conducted to develop functional food which could increase blood circulation and enhance memory. Nevertheless, people in consumption of ginkgo products, often caused severe allergic reactions due to the potential allergens identified ginkgolic acids (GAs) of ginkgo products. We first find that the extracts of Celtis sinensis leaves can reduce GAs‐induced damage on HepG2 liver cells. Then, the bioactive compounds in C. sinensis leaves were separated and purified based on anti‐inflammatory activities against T cells. Quercetin, apigenin, and isovitexin showed well anti‐inflammatory activities against Con A‐activated T‐lymphocytes and LPS activated RAW 264.7 macrophages. However, quercetin and apigenin are flavones O‐glycosides which are rich in Ginkgo biloba . To solve the problems in Ginkgo biloba products caused by GAs, flavone C‐glycoside (isovitexin) may be used for the further study in GAs toxicity‐reduction. Abstract : Traditional Chinese medicine practitioners consider that the leaves of Celtis sinensis have an excellent therapeutic effect on allergies caused by urnshiol. The obtained results indicated the extracts of C. sinensis leaves can reduce GAs‐induced damage on HepG2 liver cells. Twelve compounds were identified by bioassay‐guided isolation and isovitexin was the major flavonoid in C. sinensis leaves. Quercetin, apigenin, and isovitexin showed well anti‐inflammatory activities against Con A‐activated T‐lymphocytes and LPS activated RAW 264.7 macrophages.